Effect of Annealing on the Microstructure, Hardness, Electrical Conductivity, and Corrosion of Copper Material before Accumulative Roll Bonding Processes - M. Pita; L. Lebea (Journal of Engineering)
Copper is one of the first metals to ever be mined and used by humans, and since the dawn of civilization, it has made important contributions to behavioral science. The exploration of copper has provided knowledge of nonfuel minerals and has consequently improved society. The objective of this paper is to investigate the effect of annealing on the microstructure, mechanical properties, and corrosion of copper material before undergoing an accumulative roll bonding process (ARB). The material was heated to 600°C and cooled with water before being rolled by a two-roller rolling machine. The second ARB experiment was conducted on copper material without annealing. The samples were characterized by a light microscope (LM). The ASTM E384 test method was followed during the hardness test. The results show that annealing and applying two passes of the ARB process reduce the grain size by 37%, which is significant. It also increases copper hardness by 65% and increases its electrical conductivity by 2.6%. Additionally, the results show that the open circuit potential during the first pass heated sample was −0.07237 V; this increased by 22.16% with the second pass heated sample.